Bibliometric Exploration of Trends in the Digital Economy, E-Commerce, and ICT (2015-2025) - Cabrera Barbecho, Fanny Narcisa; Quirós Romero, Cipriano (Papeles de Europa, 2025)
The digital economy, e-commerce, and Information and Communication Technologies (ICT) have profoundly reshaped business models and socioeconomic interactions over the last decade. This study conducts a bibliometric analysis of 135 publications indexed in Scopus (2015–2025) using Bibliometrix and VOSviewer. Results reveal sustained growth in scientific interest and a strong regional concentration of academic production. The ICT–innovation–productivity triad is consolidated as the dominant conceptual axis, with emerging lines focusing on sustainable digital transformation. Future research priorities include accurately measuring the impact of digitisation on sectoral productivity, assessing e-commerce supply chain sustainability, and designing digital well-being indicators adapted to low- and middle-income contexts.
Keywords: digital economy; e-commerce; ICT; bibliometrics